UJI AKTIVITAS ANTIBAKTERI SECARA IN VIVO EKSTRAK ETANOL DAUN PAKIS SAYUR (Diplazium esculentum Swartz) PADA MENCIT JANTAN GALUR BALB/C YANG DIINFEKSI Salmonella typhi ATCC 14028 - Wahyuni Wahyuni; Fery Indradewi Armadany; Mirna Widasri (Jurnal Farmasi UIN Alauddin Makassar, 2016)
Vegetable fern leaf (Diplazium esculentumSwartz) is kind of plant that can inhibit Salmonella typhi growth. The study aimed to determine the effect of vegetable fern leaf ethanolic extract on male mice that had been infected by Salmonella typhi bacteria. Vegetable fern leaf powder was macerated with  95% ethanol and was evaporated with vacum rotary evaporator. Dosage variation of vegetable fern leaf ethanolic extract on male mice were (100; 200; 300; 400 and 500 mg/kgbb). Blood of male mice veins was cultured on agar media and  counted bacterial colonies that were formed. Study result showed increasing of vegetable fern leaf ethanolic extract could decrease the colony of Salmonella typhi that infected in male mice. Vegetable fern leaf ethanolic extract with 500 mg/kgbb could decrease 6,21% of Salmonella typhi in male mice. vegetable fern leaf ethanolic extract with dosage variation not significantly  decrease the amount of bacteria colonies in mice. Compound identification by thin layer chromatography (TLC) showed vegetable fern leaf ethanolic extract contained of  flavonoids, saponins, alkaloids, tanins and terpenoids.